The Interpretation of Mutasyabihat Verses (A Comparative Study on the Meaning of Istawa and Yad in Tafsir Fathul Qadir and Tafsir Al-Misbah) - Hilmi, Muhammad; Rhain, Ainur (Proceeding ISETH (International Summit on Science, Technology, and Humanity), 2023)
The interpretation of the mutasyabihat verses in the Qur'an is a complex problem in Islamic studies. These verses have meanings that seem ambiguous or open to various interpretations. The interpretation of the Qur'an can vary greatly depending on the context. Some differences can arise in literal versus figurative understanding, historical context, and philosophical or theological approaches in interpreting this holy text, especially in interpreting the mutasyabihat verses related to the nature of Allah, which will be the focus of our discussion in this writing. The problem is that there are still many people who make an understanding that equates the nature of Allahﷻwith creatures (Tasybih). For example, some people think that Allah sits on the 'arsy, or in other words, Allah needs his creatures. This kind of understanding is wrong understanding and can even influence the understanding of Muslim society and affect our faith as Muslims, even though we know that equating Allah with his creatures is Haram. So this study tries to explore the interpretation of the mufassir figures, namely, Imam Asy Syaukani and Quraish Shihab. Especially the interpretation of the mutasyabihat verses related to the nature of Allah. Based on the description above, this study has several study focuses: 1) How do Imam As Syaukani and Quraish Shihab interpret the meaning of istiwa in the letter al-A'raf verse 54. 2) How do Imam As Syaukani and Quraish Shihab interpret the meaning of yad in the letter sad? 75. In this study, we use Qualitative research with library methods. This study's results explain that both have broad differences in interpreting the meaning of istiwa and yad. And each uses a different method of interpretation. 1) Imam Syaukani is of the opinion that Allah resides in an unknown way. Meanwhile, Quraish Shihab assumes that the meaning of istawa is the power of Allah. 2) Imam Syaukani interprets the meaning of yad to mean "without intermediaries." Quraish Shihab interprets the meaning of yad "as an indication of the special treatment and respect that humans receive from God.”